Prisoners on Criminology: Convict Life Stories and Crime Prevention - Tregea, William (Lexington Books, 2014)
William S. Tregea makes prisoners' stories come alive with eighty prisoner essays integrated in informational chapters tracing shifts in criminality, the U.S. prison build up, and inner cities. The chapters review criminological theories through case studies of prisoners' own insights on their lives at the individual, family, and community levels.